Tone deaf and a tin ear: political leaders and listening in disasters - Ewart, Jacqui (Communication Research and Practice, 2025)
Research alludes to the inability of some politicians to listen to people affected by disasters, sometimes with disastrous consequences for those caught up in disasters and for politicians. This article suggests a new approach to engagement by politicians with disaster affected communities – that of listening. It draws on interviews with senior emergency managers in Australia, the United Kingdom, North America, Iceland and Norway, to explore their views about the need for politicians to listen in disasters. Examples are provided of instances in which the perceived inability of politicians to listen disaster survivors drew significant public attention. This article suggests a variety of ways in which politicians might effectively listen to those effected by disasters. The findings of this article have ramifications for politicians, their advisors and disaster affected communities. No Full Text